Clinical Guidelines for the Management of Adrenal Incidentaloma - Lee, Jung-Min; Kim, Mee Kyoung; Ko, Seung-Hyun; Koh, Jung-Min; Kim, Bo-Yeon; Kim, Sang Wan; Kim, Soo-Kyung; Kim, Hae Jin; Ryu, Ohk-Hyun; Park, Juri; Lim, Jung Soo; Kim, Seong Yeon; et al. (Endocrinology and metabolism (Seoul), 2017)
An adrenal incidentaloma is an adrenal mass found in an imaging study performed for other reasons unrelated to adrenal disease and often accompanied by obesity, diabetes, or hypertension. The prevalence and incidence of adrenal incidentaloma increase with age and are also expected to rise due to the rapid development of imaging technology and frequent imaging studies. The Korean Endocrine Society is promoting an appropriate practice guideline to meet the rising incidence of adrenal incidentaloma, in cooperation with the Korean Adrenal Gland and Endocrine Hypertension Study Group. In this paper, we discuss important core issues in managing the patients with adrenal incidentaloma. After evaluating core proposition, we propose the most critical 20 recommendations from the initially organized 47 recommendations by Delphi technique.